Due Process and Judicial Independence in Latin America - Medina Cuenca, Arnel; Salcedo Ortega, Ernesto; Huertas Díaz, Omar (DIXI, 2017)
Introduction: Judicial independence constitutes a guarantee of due process and one of the essential assumptions for the better operation of the judicial power. Methods: The study of a guarantee that prevents the interference of the other powers in the resolution of matters submitted to the knowledge of judges and courts is addressed by examining the main international legal instruments, constitutions and national laws, as well as the analysis of cases resolved by the national case law and the Inter-American Court of Human Rights. Results and conclusions: Issues such as how judges and magistrates are elected, the duration of their office, performance evaluations and external interference in their actions are approached from both doctrinal approaches and comparative law, aiming at measuring the degree of people’s confidence in their judicial system, as a fundamental part of democracy.